1997
DOI: 10.1128/jb.179.2.541-543.1997
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase phylogeny and the molybdenum dependence of nitrogen fixation in Methanococcus maripaludis

Abstract: We studied the effects of molybdenum, vanadium, and tungsten on the diazotrophic growth of Methanococcus maripaludis. Mo stimulated growth, with a maximal response at 4.0 M, while V had no effect at any concentration tested. W specifically inhibited diazotrophic growth in the presence of Mo. Coupling the results of our analysis and other known metal requirements with phylogenies derived from nifD and nifK genes revealed distinct clusters for Mo-, V-, and Fe-dinitrogenases and suggested that most methanogens al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 17 publications
5
53
0
Order By: Relevance
“…It has been shown that bacteria possessing both nif and anf genes preferentially express their anf paralogs in the absence of molybdenum cofactor (Masepohl and Klipp, 1996;Kessler et al, 1997;Braun et al, 1999). Based on their detailed study of nitrogenase activity, nifH gene expression and nif operon structure in N. koshunensis, Noda et al (1999) had suggested that preferential expression of anfH in Kalotermitidae is related to the lack of molybdenum in sound wood, which may have favored the acquisition of a molybdenum-independent nitrogenase (that is, anfH) by their gut symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that bacteria possessing both nif and anf genes preferentially express their anf paralogs in the absence of molybdenum cofactor (Masepohl and Klipp, 1996;Kessler et al, 1997;Braun et al, 1999). Based on their detailed study of nitrogenase activity, nifH gene expression and nif operon structure in N. koshunensis, Noda et al (1999) had suggested that preferential expression of anfH in Kalotermitidae is related to the lack of molybdenum in sound wood, which may have favored the acquisition of a molybdenum-independent nitrogenase (that is, anfH) by their gut symbionts.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of nifK, the nifE and nifN genes, which are essential for FeMo-cofactor assembly (Dean et al 1993), are found in a separate operon. In Archaea, genes homologous to the bacterial nif genes have been identified, and nitrogen fixation has been observed in several methanogenic species (Lobo and Zinder 1992, Young 1992, Bult et al 1996, Chien and Zinder 1996, Haselkorn and Buikema 1996, Kessler et al 1997, Smith et al 1997. The discovery of genes homologous to nifH, nifD and nifK suggests that the basic mechanism of nitrogen fixation is similar in Bacteria and Archaea and predicts that most methanogenic nitrogenases contain a molybdenum-cofactor Zinder 1996, Kessler et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two genes in M. barkeri that are phylogenetically related to functional nifH genes (19) allows for the possibility that both molybdenum and vanadium nitrogenases are present in this organism, and recently a vanadium nitrogenase has been confirmed (25a). In M. maripaludis, molybdenum was clearly required for diazotrophic growth (26). Vanadium failed to stimulate, and tungsten inhibited, so this species may contain a single nitrogenase of the molybdenum type.…”
Section: Metalsmentioning
confidence: 94%
“…Vanadium failed to stimulate, and tungsten inhibited, so this species may contain a single nitrogenase of the molybdenum type. The presence of molybdenum nitrogenases in other methanogens is corroborated by nif gene phylogeny (26), and by the apparent absence from the nif gene clusters of a gene corresponding to vnfG or anfG, which encode the δ subunits of alternative nitrogenases in Bacteria (27). Thus, molybdenum nitrogenases seem to predominate in methanogens, but vanadium nitrogenases may be present as well.…”
Section: Metalsmentioning
confidence: 99%